Residential, soil and water radon surveys in north-western part of Romania. (January 2017) - Cucoş (Dinu), Alexandra; Papp, Botond; Dicu, Tiberius; Moldovan, Mircea; Burghele, Denissa Bety; Moraru, Ionuţ Tudor; Tenţer, Ancuţa; Cosma, Constantin
Abstract: The exposure to radon and radon decay products in homes and at workplaces represents the greatest risk from natural ionizing radiation. The present study brings forward the residential, soil and water radon surveys in 5 counties of Romania. Indoor radon measurements were performed by using CR-39 track detectors exposed for 3 months on ground-floor level of dwellings, according to the NRPB Measurements Protocol. Radon concentrations in soil and water were measured using the LUK3C device. The indoor radon concentrations ranged from 5 to 2592 Bq⋅m −3 with an updated preliminary arithmetic mean of 133 Bq⋅m −3, and a geometric mean of 90 Bq⋅m −3 . In about 6% of the investigated grid cells the indoor radon concentrations exceed the threshold of 300 Bq⋅m −3 . The soil gas radon concentration varies from 0.8 to 169 kBq⋅m −3, with a geometric mean of 28.4 kBq⋅m −3 . For water samples, the results show radon concentrations within the range of 0.3–352 kBq⋅m −3 with a geometric mean of 7.7 Bq⋅L −1 . The indoor radon map was plotted on a reference grid developed by JRC with the resolution 10 × 10 km 2 . Highlights: The residential, soil and water radon surveys in 5 counties of Romania are presented. The indoor radon concentrations range from 5 to 2592 Bq⋅m −3 with a mean value of 133 Bq⋅m −3 . About 6% of the investigated dwellings exceed the threshold of 300 Bq⋅m −3 . The soil gas radon concentration varies from 0.8 to 169 kBq⋅m −3, with a geometric mean of 28.4 kBq⋅m −3 . The results for water samples show radon concentrations in the range of 0.3–352.2 kBq⋅m −3 with a geometric mean of 7.7 kBq⋅m −3 .